TAF(II)40 Protein Is Encoded by the e(y)1 Gene: Biological Consequences of Mutations - Soldatov, Aleksei (American Society for Microbiology, 1999)
The enhancer of yellow 1 gene, e(y)1, of Drosophila melanogaster has been cloned and demonstrated to encode the TAF(II)40 protein. The e(y)1 gene is expressed in females much more strongly than in males due to the accumulation of e(y)1 mRNA in the ovaries. Two different e(y)1 mutations have been obtained. The e(y)1(ul) mutation, induced by the insertion of Stalker into the coding region, leads to the replacement of 25 carboxy-terminal amino acids by 17 amino acids encoded by the Stalker sequences and to a decrease of the e(y)1 transcription level. The latter is the main cause of dramatic underdevelopment of the ovaries and sterility of females bearing the e(y)1 mutation. This follows from the restoration of female fertility upon transformation of e(y)1(u1) flies with a construction synthesizing the mutant protein. The e(y)1(P1) mutation induced by P element insertion into the transcribed nontranslated region of the gene has almost no influence on the phenotype of flies. However, in combination with the ph(P1) mutation, which leads to a strong P element-mediated suppression of e(y)1 transcription, this mutation is lethal. Genetic studies of the e(y)1(u1) mutation revealed a sensitivity of the yellow and white expression to the TAF(II)40/e(y)1 level. The su(Hw)-binding region, Drosophila insulator, stabilizes the expression of the white gene and makes it independent of the e(y)1(u1) mutation.